Dinamika Kelembagaan Kemitraan Usaha Rantai Pasok Buah Tropika Berorientasi Ekspor - nFN Saptana; Atika Dyah Perwita; Valeriana Darwis; Sri Hastuti Suhartini (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2018)
The main problem faced in the development of Indonesia's tropical fruits are the lack of variety, quantity, quality and continuity of supply that is in line with market demand dynamics and consumer preferences. The purpose of this paper is to examine the performance of export-oriented tropical fruit business partnership institutions. The method of analysis is carried out by reviewing various literature studies, especially primary scientific journals and other data and information. Indonesia's main tropical fruits are mango, pineapple, papaya, and avocado, constituting 75% of global tropical fruit production. National fruit production sequentially from the largest are banana of 6,189,052 tons, mango 2,376,339 tons, papaya 906,312 tons, durian 888,130 tons, and mangosteen 190,294 tons. Fruit consumption level in 2000 had reached 36 kg/capita/year, increasing in 2005 to 45 kg/capita/year, in 2007 it had reached 47 kg/capita/year, but in 2011 it decreased to 34.55 kg/capita/year, and in 2014 it increased again to 43.33 kg/capita/year. In the period January to March 2018 the volume of Indonesian fruit exports amounted to 325,236 tons, while in the same period in 2017, the volume of Indonesian fruit exports was recorded at 306,441 tons, an increase of 6.13%. Institutional performance of supply chain partnerships in tropical fruits, both carried out through general trade patterns and contract farming has not been fully efficient. The strategy of developing export-oriented tropical fruits in the future needs to be carried out through integrated supply chain business partnership institutions. Operationally can be done by using seeds/superior clone seeds, cultivation technology based on Standard Operational Procedure (SOP) and the application of Good Agricultural Practices (GAP), the application of Good Handling Practices (GHP), and integrated supply chain business partnerships. AbstrakPermasalahan pokok yang dihadapi dalam pengembangan buah tropika Indonesia adalah belum terwujudnya ragam, kuantitas, kualitas, dan kesinambungan pasokan yang sesuai dengan dinamika permintaan pasar dan preferensi konsumen. Tujuan tulisan ini adalah untuk mengkaji kinerja kelembagan kemitraan usaha buah tropika berorientasi ekspor. Metode penulisan dengan melakukan review dari berbagai studi pustaka terutama jurnal ilmiah primer serta data dan informasi terkait. Buah tropika utama Indonesia adalah mangga, nenas, papaya, dan alpukat, merupakan 75% produksi buah tropika global. Produksi buah nasional secara berturut-turut adalah pisang sebesar 6.189.052 ton, mangga 2.376.339 ton, pepaya 906.312 ton, durian 888.130 ton, dan manggis sebesar 190.294 ton. Tingkat konsumsi buah pada tahun 2000 sudah mencapai 36 kg/kapita/tahun, meningkat pada tahun 2005 menjadi 45 kg/kapita/tahun, tahun 2007 telah mencapai 47 kg/kapita/tahun, namun pada tahun 2011 mengalami penurunan menjadi sebesar 34,55 kg/kapita/tahun, dan tahun 2014 meningkat kembali mencapai 43.33 kg/kapita/tahun. Pada periode Januari hingga Maret 2018 volume ekspor buah Indonesia sebesar 325.236 ton, sedangkan periode yang sama pada tahun 2017, volume ekspor buah Indonesia tercatat sebesar 306.441 ton atau meningkat sebesar 6,13%. Kinerja kelembagaan kemitraan usaha rantai pasok pada buah tropika baik yang dilakukan melalui pola dagang umum maupun pertanian kontrak (contract farming) belum sepenuhnya efisen. Strategi pengembangan buah tropika berorientasi ekspor ke depan perlu dilakukan melalui kelembagaan kemitraan usaha rantai pasok secara terpadu. Secara operasional dapat dilakukan dengan menggunaan bibit/benih klon unggul, teknologi budidaya yang didasarkan Standar Prosedur Operasional (SOP) dan penerapan Good Agricultural Practices (GAP), penerapan Good Handling Practices (GHP), dan kelembagaan kemitraan usaha rantai pasok secara terpadu.